Management of Challenging Psoriasis Clinical Scenarios - Linda Stein Gold; Andrew Alexis; Brad P. Glick; Mona Shahriari; Eingun James Song; Bruce Strober; Najat M. Watch; Melodie Young (Dermatology and Therapy)
Abstract Psoriasis, a chronic inflammatory skin condition, can have a significant impact on patients’ quality of life. Adoption of novel and emerging treatments has significantly improved psoriasis care in clinical practice, but challenges remain. The ‘Bridging the Gaps in Challenging Psoriasis’ meeting was held in October 2024 to discuss relevant evidence, knowledge gaps, and best practices pertaining to challenging presentations of psoriasis. This report captures important insights and practice impacting guidance gathered from the panel discussion on five topics. The meeting commenced with an in-depth discussion on managing psoriasis in high-impact areas (e.g., scalp, intertriginous regions, nails, and the palms and soles) followed by a discussion on the importance of identifying and addressing common comorbidities associated with psoriasis. The panel explored key considerations and unique challenges when treating psoriasis in patients with darker skin tones (‘skin of color’) and highlighted the need for tailored therapeutic approaches. A comprehensive dialogue ensued on strategies for managing primary and secondary treatment failures. The session concluded with a concise discussion on the future of psoriasis treatments and pharmacologic therapies currently being developed to manage psoriasis. While discussing various challenging psoriasis scenarios, the dermatology experts emphasized the need to approach psoriasis as a systemic disease and advocated for comprehensive management that addresses both the skin and the broader health of the patient.